Effect of Different Regions and Ensiling Periods on Fermentation Quality and the Bacterial Community of Whole-Plant Maize Silage - Yuan Huang (Frontiers Media S.A., 2021)
This study aimed to explore the changes in the microbial community on the silage material surface and during the ensiling process of whole-plant maize in different regions. Whole-plant maize silages were sampled in Ziyun, Guanling, and Weinning counties within warm and humid climate areas in southern China. Silages were sampled at 0, 2, 5, 10, 20, and 45 days during ensiling. The nutritional components, fermentation properties, and microbiomes were examined to evaluate the influence of sampling area and fermentation time on the quality of silage. The results showed that the pH values of all silages significantly decreased (<4.2 at ensiling day 2) during fermentation and all silages achieved satisfactory fermentation at 45 days. Butyric acid was not detected during ensiling, and the contents of acetic acid and ammonia nitrogen in the final silages were below 6 g/kg DM and 50 g/kg total nitrogen, respectively. Weissella was the dominant epiphytic bacteria of raw material in Ziyun and Weinning, while Lactobacillus was prevalent in Guanling. Lactobacillus dominated the ensiling process, and its abundance significantly increased with increasing fermentation time in the three groups. Lactobacillus was negatively correlated with pH of all silages (p < 0.05) and positively correlated with lactic acid, propionic acid and acetic acid (p < 0.05). Furthermore, the bacterial community was significantly correlated with environmental factors. Altitude had a highly positive correlation with the abundance of Stenotrophomonas, Chryseobacterium, and Massilia (p < 0.01), while precipitation was negatively correlated with these bacteria. The humidity and average temperature significantly influenced the Lactobacillus and Weissella abundances of fresh whole-plant maize. During the ensiling process, the silages from three regions had similar bacterial dynamic changes, and the Lactobacillus formed and maintained good fermentation characteristics in whole-plant maize silage.